Boosting Confidence and Fluency in Speaking Comprehension through Story-Relay Activity - Moch Affan Heryana Santana; Windy Citra Negara; Linda Mayasari (PROCEEDING UMSURABAYA, 2026)
This Classroom Action Research activity examines how a structured story-relay activity in recount text improves Grade 10 EFL students’ self-confidence and speaking fluency. A total of 31 students from an Indonesian high school participated in two cycles of intervention. The first cycle is to check their confidence and their ability to speak, while the second is to apply the treatment of story relay. Pre- and post-intervention assessments of self-record video conducted outside the normal learning activity and will be compared. Both assessment were conducted using two validated rubrics: one measuring fluency (flow of speech, grammatical accuracy, narrative structure, and pronunciation) and the other assessing confidence (body language, eye contact, vocal volume, and expressive intonation), each rated on a four-point scale (1 = needs significant improvement to 4 = excellent). After collecting both data of pre- and post-assessment, both data will be compared to see how far the improvement after the treatment of story-relay on their confidence and ability to speak. Findings demonstrate that collaborative, form-focused narrative tasks can effectively foster both linguistic competence and learner confidence in an EFL context. The study recommends integrating story-relay activities as a regular classroom strategy to reinforce students’ speaking fluency and self-confidence.